DIGITAL ECONOMY AND ECONOMIC GROWTH (Conferencea, 2023)
This article is devoted to the issues of the digital economy and economic growth. in particular, the author reveals the impact of the digital economy on economic growth, gives the concept of the digital economy, analyzes the process of digitalization in various segments of the economy of Uzbekistan, as well as China, the USA, Japan and European countries.